Posted by carolina on Tuesday, August 28, 2007 at 6:47pm.
x + (-9) = -5
x = -5 + 9
x = 4
but why does X = -5 +9
If A = B, then that implies that:
A + a = B + a
for any number a.
So, if
X + (-9) = -5
then choosing a = 9 we get:
X + (-9) + 9 = -5 + 9
Since (-9) + 9 = 0 we have
X = -5 + 9
You need to get the unknown on one side of the equation and the knowns on the other side. To do that you subtract -9 from the left side, change the sign and add it to the right side.
i still don't get it
ii still don't get it
Let's try this.
X+(-9)=-5
Remember, you can do anything to an equation as long as you do it to both sides. We want to get X (the unknown) on one side and the numbers on the other with the = sign between.
So, remove the parentheses first to obtain (remember that a + sign in front of the parentheses leaves the sign of the numbers inside the parentheses unchanged--conversely, a - sign in front of the parentheses changes all the signs inside the parentheses when the parentheses are removed).
X - 9 = -5
Now add +0 to both sides.
X-9+9 = -5+9
Now combine the numbers
-9 and +9 add to zero on the left while -5 and +9 add to +4 on the right.
X = +4.
That is the way to move anything from one side to the other. If you wish to move a + number simply subtract that number from both sides; if you wish to move a - number simply add that number to both sides. An easier way is to move anything from one side to the other by moving it and changing the sign.
I hope this helps.
yes thanx now i get it